Silicon carbide nanolayers as a solar cell constituent. Issue 1 (11th September 2014) - Zakhvalinskii, V.; Piliuk, E.; Goncharov, I.; Simashkevich, A.; Sherban, D.; Bruc, L.; Curmei, N.; Rusu, M.
<x xml:space="preserve">Abstract</x> Thin films of predominantly amorphous n‐type SiC were prepared by non‐reactive magnetron sputtering in an Ar atmosphere. A previously synthesized SiC was used as a solid‐state target. Deposition was carried out on a cold substrate of p‐type Si (100) with a resistivity of 2 Ωcm. The Raman spectrum shows a dominant band at 982 cm−1, i.e., in the spectral region characteristic for SiC. It was found that the root mean square roughness varies from about 0.3 nm to 9.0 nm when the film thickness changes from about 2 nm to 56 nm, respectively. Transmission electron microscopy studies showed that SiC thin films consist predominantly of an amorphous phase with inclusions of very fine nanocrystallites. A heterostructure consisting of a p‐type Si (100) and a layer of predominantly amorphous n‐type SiC was fabricated and studied. The investigation of its electrical and photoelectric properties shows that the entire space charge region is located in Si. This is in addition confirmed by the spectral dependence of the p‐Si/n‐SiC photosensitivity. The barrier height at the p‐Si/n‐SiC interface estimated from dark I–V characteristics is of the order of 0.9–1.0 eV. Load I–V characteristics of p‐Si/n‐SiC‐nanolayer solar cells demonstrate under standard AM1.5 illumination conditions a conversion efficiency of 7.22%.